Gardens in the sky: Emotional experiences in the communal spaces at height in the Pinnacle@Duxton, Singapore. (August 2018) - Hadi, Yuri; Heath, Tim; Oldfield, Philip
Abstract: A boom in high-rise construction and vertical living has resulted in an increase in privately and publicly accessible communal spaces at height within tall buildings. Asia is leading the way in these developments, with one of the most notable projects being the Pinnacle@Duxton in Singapore. Here, seven towers are interlinked by a series of skygardens providing a continuous pathway at the 26th and 50th storeys, accommodating a mixture of functions and spaces. This study intersects literature from the fields of architecture, urban design, skyscraper geography and emotional geographies with observational analysis and interviews to identify and analyse the experiences and emotions of the various stakeholders – the architect, client, building manager and residents – involved in the creation and occupation of skygardens. The results highlight a fear of outsiders and anti-social behaviour among the authorities stewarding the building, explicitly related to the verticality of communal spaces at height. This has manifested in stringent rules governing this otherwise generous social infrastructure, provoking feelings of frustration in the residents and contested ownership between the stakeholders. However, the results also emphasise opportunities for positive emotions to emerge, providing sensations of peace and escapism within these open green spaces at height, lessening the effects of over-crowding and stress often perceived in high-density living. Highlights: The experiences and emotions of skygarden users and stakeholders is explored. Management fear of anti-social behaviour increases at height. Stringent rules in the skygardens fuel a sense of frustration in the residents. A sense of contested ownership exists between residents and skygarden management. Skygardens provide an opportunity for escapism from dense vertical living.